Effect of diet change in healthy dogs with subclinical cardiac biomarker or echocardiographic abnormalities. (14th April 2022) - Haimovitz, Dana; Vereb, Michelle; Freeman, Lisa; Goldberg, Robert; Lessard, Darleen; Rush, John; Adin, Darcy
Abstract: Background: A recent study showed higher high‐sensitivity cardiac troponin I (hs‐cTnI) concentrations in healthy dogs eating grain‐free (GF) compared to those eating grain‐inclusive (GI) diets. Hypothesis/Objectives: Healthy dogs with subclinical cardiac abnormalities eating GF diets at baseline will show improvements in cardiac biomarkers and echocardiographic variables after diet change, whereas healthy dogs eating GI diets at baseline will not improve. Animals: Twenty healthy dogs with subclinical cardiac abnormalities (12 Golden Retrievers, 5 Doberman Pinschers, 3 Miniature Schnauzers). Methods: This prospective study included dogs with increased hs‐cTnI or N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) concentrations, or echocardiographic abnormalities. Mixed modeling was used to evaluate echocardiographic, hs‐cTnI, and NT‐proBNP differences between groups (GF or GI diet at baseline) over time (1 y after diet change). Results: Ten GF and 10 GI dogs were evaluated. There were statistically significant time: group interactions for hs‐cTnI ( P  = .02) and normalized left ventricular internal systolic diameter (LVIDsN; P  = .02), with GF dogs showing larger decreases in these variables than GI dogs. Median (range) hs‐cTnI (ng/mL) for GF dogs was 0.141 (0.012‐0.224) at baseline and 0.092 (0.044‐0.137) at 1 y, and for GI dogs was 0.051 (0.016‐0.195) at baseline and 0.060 (0.022‐0.280) at 1 y. Median LVIDsN for GF dogs was 1.01 (0.70‐1.30) at baseline and 0.87 (0.79‐1.24) at 1 y, and for GI dogs was 1.05 (0.84‐1.21) at baseline and 1.10 (0.85‐1.28) at 1 y. Conclusions and Clinical Importance: Decreased hs‐cTnI and LVIDsN in GF dogs after diet change supports reversibility of these subclinical myocardial abnormalities.